2005
DOI: 10.2527/2005.8361332x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fecal crude protein concentration and diet organic matter digestibility in cattle1

Abstract: The positive relationship between fecal CP concentration and diet OM digestibility in cattle, which is based on increasing undigested microbial CP and decreasing fecal OM as OM digestibility increases, may be used as an indirect method for estimating diet OM digestibility from fecal CP concentration. Results of digestibility trials (445 individual observations) conducted at Hohenheim and Braunschweig, Germany, and at Gumpenstein, Austria, were used to study the relationship between CP concentration in feces (x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 14 publications
2
68
0
5
Order By: Relevance
“…However, in these experiments, sward heights after grazing were 3.0 and 6.5 cm at 21 and 35 days of regrowth, respectively. This suggests that rams at pasture have access Estimation of OMD and OMI To compare intake and digestibility between indoor feeding and pasture grazing, the CPf method was used, because previous studies showed that this method can provide consistent estimates of in vivo OMD at pasture (Boval et al, 2003;Lukas et al, 2005;Schlecht and Susenbeth, 2006). Moreover, the range of variation in CPf in the dataset used to derive the CPf equation (from 7.9% to 20.3%; Fanchone et al, 2009) was similar to that observed in our study for both indoor animals (from 14.2% to 18.0% and from 13.2% to 16.2% at 21 and 35 days of regrowth, respectively) and grazing animals (from 14.3% to 17.5% and from 17.7% to 18.2% at 21 and 35 days of regrowth, respectively; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, in these experiments, sward heights after grazing were 3.0 and 6.5 cm at 21 and 35 days of regrowth, respectively. This suggests that rams at pasture have access Estimation of OMD and OMI To compare intake and digestibility between indoor feeding and pasture grazing, the CPf method was used, because previous studies showed that this method can provide consistent estimates of in vivo OMD at pasture (Boval et al, 2003;Lukas et al, 2005;Schlecht and Susenbeth, 2006). Moreover, the range of variation in CPf in the dataset used to derive the CPf equation (from 7.9% to 20.3%; Fanchone et al, 2009) was similar to that observed in our study for both indoor animals (from 14.2% to 18.0% and from 13.2% to 16.2% at 21 and 35 days of regrowth, respectively) and grazing animals (from 14.3% to 17.5% and from 17.7% to 18.2% at 21 and 35 days of regrowth, respectively; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…For the purpose of utilising in vitro digestibility to estimate in vivo digestibility in the field, the regression equation in vivo dg = 1.01 (in vitro dg) + 8.48 could be used, although this would be specific for mixtures of these two species. Lukas et al (2005) used data from two digestibility trials, one in Germany with 257 individual comparisons (data set 1) and the other in Austria (188 comparisons, data set 2) to predict OM digestibility (y, %) using a regression based on the crude protein content of the faeces (x, g kg -1 ). The data were obtained from dairy and beef cattle confined in stalls with titanium oxide as an external indicator for faecal production.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the existing mathematical relation between digestibility values and the concentration of fecal N determined in conditions of confinement (Ferri et al, 2003) would also be seen for grazing conditions. Lukas et al (2005) found little effect of diet composition variation on the concentration of fecal N, and obtained a close relationship between OMD of and the concentration of fecal N. The main advantages of this technique are its reduced and simple analytical work and no need for diet sampling.…”
Section: Total Collection Of Feces and Omd Estimated By The Fecal N Imentioning
confidence: 91%
“…The ratio of N concentrations in fecal OM and OMD, relies on the reduction of fecal OM excretion and the increase in N fecal concentration when diet OM digestibility increases (Lukas et al, 2005). As a consequence, based on the value of NTF (g kg -1 OMI) and the concentration of N in fecal OM (cNF; g kg -1 OM), the quantity of forage OM that would determine 1000 g of fecal OM would be 1000 x cNF/NTF, and digestibility would be calculated as follow:…”
Section: Fecal N Indexmentioning
confidence: 99%